PENGEMBANGAN E-LKPD BERBASIS PENDEKATAN SAINTIFIK PADA SUB MATERI TATA NAMA SENYAWA POLIATOMIK - Novi Dwi Trisnawati; Rini Muharini; Rahmat Rasmawan; Eny Enawaty; Ira Lestari (Jurnal Education and Development, 2023)
This research to produce electronic student worksheets (E-LKPD) based on a scientific approach to the nomenclature sub-matter of polyatomic compounds that are feasible to use. This research is a development research using a 4-D model from Thiagaradjan. The data collection technique used is an indirect communication technique with a data collection tool, namely the feasibility evaluation sheet. The feasibility of the E-LKPD is seen from three aspects, namely material, language and graphics. Each aspect is assessed by each of the three experts. The results showed that the E-LKPD based on a scientific approach to the nomenclature sub-matter of polyatomic compounds was very suitable to be used as teaching material to support the learning of polyatomic compound nomenclature material with a score percentage on content and presentation aspects of 93.3% and 95.8%, language 93.3%, and 90.2% graphics.